Post-transaction brand and model line-up integration in the automotive industry: Case studies of European companies as target of acquisitions by Chinese and Indian multinational corporations - Salokoski, Kristian (fi=Turun yliopisto|en=University of Turku|, 2017)
Corporations practice company acquisitions in order to create shareholder’s value. During the last few decades, the companies in emerging markets have become active in the acquisition business. During the last decade, large and significant acquisitions have occurred especially in automotive industry. While domestic markets have become too competitive and companies are lacking required capabilities, they seek possibilities to expand into Western markets by attaining valuable assets through acquisitions of developed country corporations. This study discusses the issues and characteristics of these acquisitions through case studies. The purpose of this study was to identify the acquisition motives and strategies for post-transaction brand and product integration as well as analyze the effect of the motives to the integration strategy. The cases chosen for the research were Chinese Geely acquiring Swedish Volvo in 2010 and Indian Tata Motors buying British Jaguar Land Rover in 2008. The main topics were chosen according to their significance for companies in automotive industry as well as those are most visible parts for consumers. The study is based on qualitative case study methods, analyzing secondary data from academic papers and news articles as well as companies’ own announcements e.g. stock exchange and press releases. The study finds that the companies in the cases mainly possessed asset-seeking and market-seeking motives. In addition, the findings refer to rather minimal post-acquisition brand and product integration strategies. Mainly the parent companies left the target company autonomous to make their own business strategies and decisions. The most noticeable integrations were in the product development and production processes. Through restructuring the product architectures, the companies were able to share components and technology between product families and brands, which results in cutting down costs and in increase of profitability and efficiency. In the Geely- Volvo case, the strategy focused more on component sharing and product development know-how, whereas in Tata Motors-Jaguar Land Rover case, the main actions were to cut down costs through component sharing and combine production and distribution networks especially in Asian markets. However, it was evident that in both cases the integration and technology sharing were executed cautiously to prevent on harming the valuable image of the luxury brand. This study has concluded that the asset-seeking motives have significant influence on the posttransaction brand and model line-up integration strategies. By taking a cautious approach in acquiring assets, such as luxury brand, the companies in the cases have implemented a successful post-acquisition strategy and managed to create value for the shareholders at least in short-term. Yritykset harjoittavat yritysostoja luodakseen osakkeenomistajille lisäarvoa. Viimeisten muutamien vuosikymmenien aikana yritykset kehittyvissä maissa ovat myös aktivoituneet yritysostoissa. Viimeisen vuosikymmenen aikana erityisesti autoteollisuudessa on esiintynyt suuria ja merkittäviä yritysostoja. Koska kilpailu kotimaan markkinoilla on kiristynyt ja yritykset ovat vailla vaadittavia valmiuksia, ne etsivät mahdollisuuksiaan laajentaa länsimaisiin markkinoihin hankkimalla arvokkaita etuja kehittyneiden maiden yrityksistä yritysostojen avulla. Tämä tutkimus pohtii näiden yritysostojen olennaisia kysymyksiä ja ominaisuuksia casetutkimuksien kautta. Tutkimuksen tarkoitus oli tunnistaa sekä yritysostojen motiiveja ja brändi- ja mallisto-integraation strategioita että analysoida kyseisten motiivien vaikutusta integraatiostrategiaan. Tapaus-tutkimuksiksi valittiin kiinalaisen Geelyn yritysosto ruotsalaisesta Volvosta vuonna 2010 ja intialaisen Tata Motorsin yritysosto englantilaisesta Jaguar Land Roverista vuonna 2008. Tutkimus on kvalitatiivinen case-tutkimus ja siinä analysoidaan toissijaista tietoa sekä akateemisten ja uutisartikkeleiden että yritysten omien ilmoitusten, kuten pörssi- ja lehdistötiedotteiden, kautta. Tutkimuksen tulokset osoittavat, että tutkittujen yritysten toiminnat perustuivat motiiveihin, joita ajoivat etujen and uusien markkinoiden tarve. Sen lisäksi tutkimustulokset osoittivat, että yritysoston jälkeinen brändi- ja mallisto-integraatio pidettiin minimaalisena. Pääasiallisesti kohdeyrityksille jätettiin autonomia tehdä omat liikkeenjohdolliset päätökset yritysstrategioihin liittyen. Huomattavimmat integraatiot koskivat tuotekehityksellisiä ja tuotannollisia prosesseja. Kehittämällä uudelleen tuotearkkitehtuureja, yritykset pystyivät jakamaan komponentteja ja teknologiaa tuoteperheiden ja brändien välillä. Tämä mahdollisti kustannusleikkauksia sekä kannattavuuden ja tehokkuuden parantamista. Geely-Volvo –tapauksessa integraatiostrategia keskittyi komponenttien jakamiseen yhteisten tuotearkkitehtuurien avulla ja tuotekehityksen ammattitaitoon, kun taas Tata Motors-JLR –tapauksessa päätoiminnat olivat kustannuksien leikkaus sekä tuotannon ja jakeluverkoston yhdistäminen erityisesti Aasian maissa. Yhteistä yrityskaupoissa oli, että brändi- ja mallisto-integraatio sekä teknologian jakaminen suoritettiin varoen ehkäistäkseen arvokkaiden luksus-brändien tuotekuvan vahingoittamista. Tutkimuksen lopputulokset osoittavat, että yrityskaupan motiiveilla on huomattava vaikutus brändija mallisto-integraation strategiaan. Toteuttamalla varovaista lähestymistapaa luksus-brändin hankinnassa ja integraatiossa, yritykset ovat onnistuneet luomaan lisäarvoa osakkeenomistajille vähintään lyhyellä aikavälillä.